THE TYPES OF BULLYING AND THEIR IMPACTS IN SPEAK MOVIE BY JESSICA SHARZER - Irfan Hibatullah; Suci Budiwaty (UG Journal, 2023)
Bullying is a type of aggression that involves an imbalance of power where the bully consciously and deliberately hurt another person physically or psychologically by hurting their body, feelings, self-esteem, reputation, and property. This research aimed to find out the types of bullying that happened in Speak movie and the impacts that the character Melinda Sordino suffered in Speak movie. This research used Sheri Bauman’s theory in analyzing the types of bullying and used SEJIWA’s theory to analyze the impacts of bullying in Speak’s movie. The source of data was the Speak movie by Jessica Sharzer. In analyzing the data, the qualitative method was used. The data of this research were the scenes and dialogues in the movie that contained the types of bullying and the impacts of bullying. The results of this research showed that there were 9 data found based on the types of bullying, namely 3 data of physical bullying, 3 data of verbal bullying, and 3 data of indirect bullying. However, for the impacts of bullying, there were 12 data found, namely 2 data on academic impacts, 4 data on psychological impact, 3 data on physical impact, and 3 data on social impact.